Various Concentration Distribution of Benzil Amino Purine Concentration on Callus Growth in Apple Cucumber Originated from Karawang - Liga Nursolihah; Slamet Abadi; Nurcahyo Widyodaru Saputro (Universitas Wiralodra, 2022)
The purpose of the study is to find the best Benzil Amino Purine (BAP) concentrations and proper explants for the growth of the apple cucumber callus (Cucumis sp.) on Murashige and Skoog (MS) media. The research method used was an experimental method with nonparametric statistics with treatments A0B1 (BAP 0 + Leaves), A0B2 (BAP 0 + Stem), A1B1 (BAP 0.5 μM + Leaf), A1B2 (BAP 0.5 μM + Stem), A2B1 (BAP 1.5 μM + Leaf), A2B2 (BAP 1.5 μM + Stem), A3B1 (BAP 3.0 μM+ Leaves) and A3B2 (BAP 3.0 μM+ Stems) and analyzed descriptively using the Kruskal Wallis Test. The parameters observed were callus emergence, callus diameter, growth rate and callus morphology. The results showed accretion of an apple cucumber callus at concentration 0.5 μM BAP + stem which exerted a faster effect on callus formation time (27 hsi), 1.5 μM BAP + stem giving the largest diameter with 1.2 cm. The stem explant gives the best growth rate (0.8 cm/3 day) as well as concentrations of 0.5 μM and 1.5 μM giving the best growth rate (0.462 cm/3 day and 0.887 cm/3 day). This result showed calluses A0B2 and A1B1 (compact + green) as well as A1B2 and A2B2 (crumb + yellowish-green).